Evaluation of lead and cadmium levels in lipsticks sold in Kathmandu, Nepal, and their potential health risk assessment - Aryal, Salina; Bashyal, Narayan; Gautam, Surendra Kumar; Pokhrel, Megh Raj; Poudel, Bhoj Raj (International Journal of Applied Sciences and Biotechnology, 2021)
The study aimed to assess the levels of Lead (Pb) and Cadmium (Cd) in lipsticks and theirs associated health hazards to consumers. 13 lipsticks and 7 lipglosses were selected randomly from various shopping centers in Kathmandu, Nepal. The lipstick sample was chemically digested and analyzed using flame atomic absorption spectroscopy (FAAS). The concentration range of Pb and Cd in lipsticks was from 0.020.009 to 30.970.014 mg kg-1 and 0.010.014 to 0.920.009 mg kg-1 respectively. The hazard quotient for Pb was found greater than 1 in 15 samples showing detrimental carcinogenic health risk through lipstick consumption. So, these lipstick brands are prone to hamper human health. Accordingly, regular monitoring of the lipsticks before importing them is highly recommended.Int. J. Appl. Sci. Biotechnol. Vol 9(3): 213-219.